A new type of nano antibacterial and anti-odor tea mask

By combining nano-tea particles on the inner protective layer of the tea mask, the problems of odor and bacterial growth on the inner surface of the mask are solved, and better deodorization, antibacterial, breathable and moisture absorption effects are achieved, and wearing comfort is improved.

CN115039935BActive Publication Date: 2025-04-29TEA RESEARCH INSTITUTE CHINESE ACADEMY OF AGRICULTURAL SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210505277.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-10
Publication Date
2025-04-29
Estimated Expiration
2042-05-10

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a novel nano-antibacterial and anti-odor tea mask, and relates to the technical field of protective equipment. The novel nano-antibacterial and anti-odor tea mask of the present invention comprises an outer layer, a middle layer and an inner protective layer from the outside to the inside, and the inner protective layer comprises a non-woven fabric substrate and nano-tea particles compounded on the non-woven fabric substrate, and the nano-tea particles are made of tea leaves as raw materials, and tea extract and extraction residue are obtained after extraction, and then the extraction residue is subjected to ultrafine grinding, and then modified to obtain a tea matrix, and then the tea matrix is ​​used to load the tea extract. The present invention discloses a novel nano-antibacterial and anti-odor tea mask, which improves the inner protective layer, and composites nano-tea particles on a traditional non-woven fabric substrate, which has better deodorizing and antibacterial effects, and under the action of nano-tea particles, has better air permeability and moisture absorption properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective equipment, in particular to a novel nano antibacterial and anti-odor tea mask. Background Art

[0002] Masks are generally divided into three layers: inner, middle and outer. The inner layer is made of skin-friendly material, usually made of ordinary sanitary gauze or non-woven fabric. The middle layer is an isolation filter layer, made of ultra-fine polypropylene fiber melt-blown material. The outer layer is a special material antibacterial layer, made of non-woven fabric or ultra-thin polypropylene melt-blown material. However, due to the sealing of the mask, unpleasant odors are usually generated in the mask due to bad breath when the mask is worn. At the same time, due to the inevitable accumulation of saliva inside the mask during normal use, coupled with the warm and humid environment inside the mask, bacteria are easily grown on the inner surface of the mask.

[0003] In view of this, tea masks have been derived in the prior art, which solve the problem of odor inside the mask by adding tea leaves. However, the technical means mostly adopted are to directly fill the tea leaves into the inside of the mask, which does not bring good results and the antibacterial effect is also very limited. Summary of the invention

[0004] In view of the above problems, the purpose of the present invention is to disclose a novel nano antibacterial and anti-odor tea mask, which improves the inner protective layer and composites nano tea particles on a traditional non-woven fabric substrate, which has better deodorizing and antibacterial effects, and to a certain extent ensures the stability of tea active ingredients such as tea polyphenols, and under the action of antibacterial and deodorizing tea nanoparticles, has better air permeability and moisture absorption properties.

[0005] Specifically, the present invention provides a novel nano-antibacterial and anti-odor tea mask, which includes an outer layer, a middle layer and an inner protective layer from the outside to the inside, and the inner protective layer includes a non-woven fabric substrate and nano-tea particles composited on the non-woven fabric substrate. The nano-tea particles are made from tea leaves, and tea extract and extraction residues are obtained through extraction. The extraction residues are then ultrafinely ground and modified to obtain a tea matrix, and the tea matrix is ​​then used to load the tea extract to obtain the extraction residue.

[0006] The novel nano antibacterial and anti-odor tea mask of the present invention improves the inner protective layer and composites nano tea particles on a traditional non-woven fabric substrate. The nano tea particles are made of tea leaves, and the tea leaves themselves have certain antibacterial and deodorizing effects. The tea leaves are extracted and the extraction residues are processed to obtain antibacterial and deodorizing particles with stronger adsorption performance, which can achieve better adsorption and deodorizing effects. At the same time, the antibacterial and deodorizing particles can better absorb moisture exhaled by the human body and keep the inside of the mask dry. Compared with the traditional method of directly filling the inside of the mask with tea leaves, the antibacterial and deodorizing effects are better, the added amount is less, and the influence on the suction resistance of the mask is smaller.

[0007] Furthermore, the nano tea leaves particles are arranged on a side of the non-woven fabric substrate close to the middle layer.

[0008] Furthermore, the non-woven fabric substrate is made of polypropylene material.

[0009] Furthermore, the preparation method of the nano tea leaf particles comprises the following steps:

[0010] S1: Take dried tea leaves, add 80wt% ethanol solution, heat and reflux for extraction for 2h, filter after cooling, concentrate the filtrate by rotary evaporation to obtain tea extract, store it in a sealed container, wash the extract residue and dry it for later use;

[0011] S2: The dried extraction residue is ultrafinely ground, added to a sodium hydroxide solution, and then carbon disulfide is added, and the mixture is stirred at room temperature for 24 hours. After the reaction is completed, the mixture is centrifuged, the reaction solution is collected, and washed with deionized water until neutral. The obtained product is added to deionized water and stirred evenly, and then frozen at -80°C, and then vacuum dried to obtain a tea matrix;

[0012] S3: Take tea extract and polylactic acid-glycolic acid copolymer, add them to N, N-dimethylformamide solution, stir and mix to obtain a mixed solution, add the mixed solution to a 1wt% Tween-80 aqueous solution under stirring, and after the addition is completed, continue to stir and react for 24 hours. After the reaction is completed, place the reaction product in a dialysis bag and dialyze it for 24 hours;

[0013] S4: freeze-dry the solution in the dialysis bag, add the pretreated tea matrix, stir and mix, spray the chitosan solution with a nano nozzle, and dry to obtain nano tea particles.

[0014] During the preparation process, the tea extract is first wrapped with polylactic acid-glycolic acid copolymer to protect the tea extract and prevent its effective ingredients from being oxidized by the outside air, thereby ensuring the stability and activity of the antibacterial function of the nano-tea particles to a certain extent.

[0015] Furthermore, the tea leaves are a mixture of one or more of green tea, black tea, oolong tea, white tea and jasmine tea.

[0016] Furthermore, in the step S4, the pretreatment of the tea substrate is specifically as follows: dissolving acrylic acid in water, adding 20wt% sodium hydroxide solution to adjust the pH to 5-6, then adding the tea substrate, stirring and dispersing evenly, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, heating to 60-70°C, stirring and reacting for 3-5 hours, filtering after the reaction is completed, soaking the filter cake in distilled water for 4-6 hours, then rinsing with deionized water for 3-5 times, and drying.

[0017] The tea matrix is ​​grafted with acrylic acid for pretreatment. Acrylic acid has good hydrophilic properties. Introducing it into the surface of the tea matrix can, on the one hand, increase the hydrophilicity of the tea matrix, thereby increasing the hydrophilicity of the non-woven fabric substrate and improving its water absorption performance. On the other hand, the introduction of acrylic acid can increase the bonding between the tea matrix and the non-woven fabric substrate, so that it can be better loaded on the non-woven fabric substrate to avoid falling off during use or storage.

[0018] Furthermore, the preparation method of the inner protective layer is: activating the non-woven fabric substrate to obtain an activated non-woven fabric substrate, then taking the nano-tea particles and adding them to the tea extract water, stirring and dispersing to obtain a suspension, laying the activated non-woven fabric substrate horizontally on a tray, spraying the suspension onto the surface of the activated non-woven fabric substrate, and then performing high-energy electron irradiation treatment under a nitrogen atmosphere, repeating the spraying and irradiation treatment 2-3 times to obtain the inner protective layer.

[0019] Furthermore, the activation treatment is as follows: taking the non-woven fabric substrate, boiling it with a sodium carbonate aqueous solution for 40 minutes, taking it out, washing it with clean water until it is neutral, and drying it to a constant weight.

[0020] Furthermore, the amount of the nano-tea leaf particle suspension sprayed each time is 8-10 g / ㎡.

[0021] By limiting the amount of suspension sprayed, the amount of nano-tea particles added can be limited. If it is too much, the antibacterial and deodorizing particles will affect the air permeability. If it is too little, the effect will be poor. At the same time, under the addition amount of the present invention, the suspension will not soak into the bottom surface of the non-woven fabric substrate. Therefore, the overall cross-section of the non-woven fabric substrate is close to the middle layer, and the hydrophilicity increases, thereby further improving the air permeability and moisture absorption permeability of the non-woven fabric substrate, and preventing the water vapor exhaled by the human body from gathering on the inner surface of the mask.

[0022] Beneficial effects of the present invention:

[0023] The invention discloses a novel nano antibacterial and anti-odor tea mask, which improves the inner protective layer and composites nano tea particles on a traditional non-woven fabric substrate, has better deodorizing and antibacterial effects, and under the action of the antibacterial and deodorizing particles, has better air permeability and moisture absorption performance, can ensure the dryness of the inside of the mask to a certain extent, and improve wearing comfort. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Scanning electron microscope image of the nano tea particles of Example 1;

[0025] Figure 2 The curve of the particle size and size distribution of nano tea particles changing with time;

[0026] Figure 3 The agar plate method was used to evaluate the inhibitory effect of nano-tea particles on PA growth at different concentrations. DETAILED DESCRIPTION

[0027] The present invention will be described in detail below with reference to specific embodiments:

[0028] The invention discloses a nano antibacterial and anti-odor tea mask, which comprises an outer layer, a middle layer and an inner protective layer from the outside to the inside, wherein the inner protective layer comprises a non-woven fabric substrate and nano tea particles composited on the non-woven fabric substrate, wherein the nano tea particles are arranged on a side of the non-woven fabric substrate close to the middle layer, wherein the non-woven fabric substrate is a polypropylene material, wherein the nano tea particles are made from tea leaves, and a tea extract and an extraction residue are obtained by extracting the tea extract and then modifying the extraction residue to obtain a tea matrix, and then the tea matrix is ​​loaded with the tea extract, as follows:

[0029] Embodiment 1

[0030] Preparation of antibacterial and deodorizing nano green tea particles

[0031] S1: Take dried green tea leaves, add 80wt% ethanol solution of 12 times the weight of the tea leaves, heat to 60℃, keep warm and reflux for 2h, filter after cooling, and concentrate the filtrate by rotary evaporation until there is no alcohol taste to obtain tea extract, which is sealed and stored, and the extraction residue is washed and dried for later use;

[0032] S2: After the dried extraction residue is ultrafinely ground, 2 g is weighed and added to 100 ml of 15 wt% sodium hydroxide solution, and then 5 ml of carbon disulfide is added, and the mixture is stirred and reacted at room temperature for 24 hours. After the reaction is completed, the mixture is centrifuged, the reaction liquid is collected, and washed with deionized water until neutral. The obtained product is added to deionized water and stirred evenly, and then frozen at -80°C and vacuum dried to obtain a tea matrix;

[0033] S3: Weigh tea extract and polylactic acid-glycolic acid copolymer (PLGA, LA:GA=50:50, Mw=5000Da) in a mass ratio of 1:5, and add them to N,N-dimethylformamide solution with a mass of 10 times that of tea extract respectively, stir and mix to obtain a mixed solution, and slowly add the mixed solution to an aqueous solution containing 1wt% Tween-80 at a rate of 1-2 / s under a stirring speed of 300r / s, the volume ratio of N,N-dimethylformamide solution to Tween-80 aqueous solution is 1:9, and stir and react for 24h. After the reaction is completed, place the reaction product in a dialysis bag (dialysis bag retention mass=3500Da) and dialyze for 24h to remove the organic solvent N,N-dimethylformamide;

[0034] S4: dissolving acrylic acid in water to obtain an acrylic acid solution with a mass concentration of 10%, adding 20wt% sodium hydroxide solution to adjust the pH to 5-6, and then adding tea substrate at a solid-liquid ratio of 1:10, stirring and dispersing evenly, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, the mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and acrylic acid is 0.2:0.3:1, heating to 65°C, stirring and reacting for 4 hours, filtering after the reaction is completed, soaking the filter cake with distilled water for 6 hours, and then rinsing it with deionized water for 4 times, and drying it to obtain a pretreated tea substrate;

[0035] The solution in the dialysis bag was freeze-dried, and the pretreated tea matrix was added. After stirring and mixing, 1 wt% chitosan solution was added by spraying with a nano nozzle. The spraying amount of chitosan solution was 2 ml / 10 g, and the nano tea particles were obtained by drying.

[0036] Tea Extract

[0037] The prepared nano-tea leaves were tested for their morphology and size using a transmission electron microscope (TEM). Figure 1 shown.

[0038] The preparation of TEM samples is as follows: drop a drop (10 μL) of uniformly dispersed nano-tea particle suspension (0.5 mg / mL) on the front of a copper mesh (400 mesh) coated with a carbon film, leave for 1 minute, blot dry with filter paper, and repeat 3-5 times. Then drop 10 μL of 2% (w / v) phosphotungstic acid solution on the front of the copper mesh, leave for 1 minute, blot dry with filter paper, and repeat 3 times. Finally, use secondary water to wash the excess phosphotungstic acid remaining on the copper mesh. The steps are the same as above. The secondary water is filtered with a 0.22 μm pore size filter membrane in advance. Drop 10 μL of secondary water on the copper mesh, leave for 1 minute, blot dry with filter paper, and repeat 3 times. Put the copper mesh in an oven at 60°C overnight, and then observe under a microscope. In the TEM image, the average particle size is calculated by measuring the diameters of 10 nanoparticles, from Figure 1 It can be seen that the nano tea particles are spherical and the average particle size is about 50nm

[0039] Preparation of inner protective layer

[0040] Take a non-woven fabric substrate, soak it in a 2wt% sodium carbonate aqueous solution, boil it for 40 minutes, take it out, wash it with clean water until it is neutral, and dry it to constant weight to obtain an activated non-woven fabric substrate. Then take the antibacterial and deodorizing nano green tea particle tea extract and add water to adjust the solid-liquid ratio to 5g / L. After stirring and dispersing, a suspension is obtained. The activated non-woven fabric substrate is horizontally spread on a tray, and the suspension is sprayed onto the surface of the activated non-woven fabric substrate. The spraying amount is 9g / ㎡, and then high-energy electron irradiation treatment is carried out under a nitrogen atmosphere. The irradiation dose is 40kGy. The spraying and irradiation treatment are repeated 3 times to obtain an inner protective layer.

[0041] The prepared inner protective layer is compounded with the middle layer and the outer layer using an existing conventional method to obtain the nano antibacterial and anti-odor tea mask of the present application.

[0042] Embodiment 2

[0043] Preparation of antibacterial and deodorizing nano black tea particles

[0044] S1: Take dried black tea leaves, add 80wt% ethanol solution of 11 times the weight of the tea leaves, heat to 70℃, keep warm and reflux for 2h, filter after cooling, and concentrate the filtrate by rotary evaporation until there is no alcohol taste to obtain tea extract, which is sealed and stored, and the extraction residue is washed and dried for later use;

[0045] S2: After the dried extraction residue is ultrafinely ground, 2 g is weighed and added to 100 ml of 15 wt% sodium hydroxide solution, and then 6 ml of carbon disulfide is added, and the mixture is stirred and reacted at room temperature for 24 hours. After the reaction is completed, the mixture is centrifuged, the reaction liquid is collected, and washed with deionized water until neutral. The obtained product is added to deionized water and stirred evenly, and then frozen at -80°C and vacuum dried to obtain a tea matrix;

[0046] S3: Weigh tea extract and polylactic acid-glycolic acid copolymer (PLGA, LA:GA=50:50, Mw=5000Da) in a mass ratio of 1:5, and add them to N,N-dimethylformamide solution with a mass of 10 times that of tea extract respectively, stir and mix to obtain a mixed solution, and slowly add the mixed solution to an aqueous solution containing 1wt% Tween-80 at a rate of 1-2 / s under a stirring speed of 300r / s, the volume ratio of N,N-dimethylformamide solution to Tween-80 aqueous solution is 1:9, and stir continuously for 24h. After the reaction is completed, place the reaction product in a dialysis bag (dialysis bag retention mass=3500Da) and dialyze for 24h to remove the organic solvent N,N-dimethylformamide;

[0047] S4: dissolving acrylic acid in water to obtain an acrylic acid solution with a mass concentration of 9%, adding 20wt% sodium hydroxide solution to adjust the pH to 5-6, and then adding tea substrate according to a solid-liquid ratio of 1:12, stirring and dispersing evenly, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, the mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and acrylic acid is 0.2:0.3:1, heating to 70°C, stirring and reacting for 3 hours, filtering after the reaction is completed, soaking the filter cake with distilled water for 4 hours, and then rinsing it with deionized water for 5 times, and drying it to obtain a pretreated tea substrate,

[0048] The solution in the dialysis bag is freeze-dried, and the pretreated tea matrix is ​​added. After stirring and mixing, the tea extract is sprayed with a nano nozzle and 1wt% chitosan solution is added. The spraying amount of the chitosan solution is 1.5ml / 10g, and the antibacterial and deodorizing nano tea particles are obtained by drying.

[0049] Preparation of inner protective layer

[0050] Take a non-woven fabric substrate, soak it in a 2wt% sodium carbonate aqueous solution, boil it for 40 minutes, take it out, wash it with clean water until it is neutral, and dry it to constant weight to obtain an activated non-woven fabric substrate. Then take the antibacterial and deodorizing nano black tea particle tea extract and add water to adjust the solid-liquid ratio to 5g / L. After stirring and dispersing, a suspension is obtained. The activated non-woven fabric substrate is horizontally spread on a tray, and the suspension is sprayed onto the surface of the activated non-woven fabric substrate. The spraying amount is 10g / ㎡, and then high-energy electron irradiation treatment is carried out under a nitrogen atmosphere. The irradiation dose is 40kGy. The spraying and irradiation treatment are repeated twice to obtain an inner protective layer.

[0051] The prepared inner protective layer is compounded with the middle layer and the outer layer using an existing conventional method to obtain the nano antibacterial and anti-odor tea mask of the present application.

[0052] Embodiment 3

[0053] Preparation of antibacterial and deodorizing nano white tea particles

[0054] S1: Take dried white tea leaves, add 80wt% ethanol solution of 10 times the weight of the tea leaves, heat to 65℃, keep warm and reflux for 2h, filter after cooling, and concentrate the filtrate by rotary evaporation until there is no alcohol taste to obtain tea extract, which is sealed and stored, and the extraction residue is washed and dried for later use;

[0055] S2: After the dried extraction residue is ultrafinely ground, 3 g is weighed and added to 100 ml of 15 wt% sodium hydroxide solution, and then 5 ml of carbon disulfide is added, and the mixture is stirred and reacted at room temperature for 24 hours. After the reaction is completed, the mixture is centrifuged, the reaction liquid is collected, and washed with deionized water until neutral. The obtained product is added to deionized water and stirred evenly, and then frozen at -80°C and vacuum dried to obtain a tea matrix;

[0056] S3: Weigh tea extract and polylactic acid-glycolic acid copolymer (PLGA, LA:GA=50:50, Mw=5000Da) in a mass ratio of 1:5, and add them to N,N-dimethylformamide solution with a mass of 10 times that of tea extract respectively, stir and mix to obtain a mixed solution, and slowly add the mixed solution to an aqueous solution containing 1wt% Tween-80 at a rate of 1-2 / s under a stirring speed of 300r / s, the volume ratio of N,N-dimethylformamide solution to Tween-80 aqueous solution is 1:9, and stir and react for 24h. After the reaction is completed, place the reaction product in a dialysis bag (dialysis bag retention mass=3500Da) and dialyze for 24h to remove the organic solvent;

[0057] S4: dissolving acrylic acid in water to obtain an acrylic acid solution with a mass concentration of 8%, adding 20wt% sodium hydroxide solution to adjust the pH to 5-6, and then adding tea substrate according to a solid-liquid ratio of 1:8, stirring and dispersing evenly, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, the mass ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and acrylic acid is 0.2:0.3:1, heating to 60°C, stirring and reacting for 5 hours, filtering after the reaction is completed, soaking the filter cake with distilled water for 5 hours, and then rinsing with deionized water for 3 times, drying to obtain a pretreated tea substrate;

[0058] The solution in the dialysis bag is freeze-dried, and the pretreated tea matrix is ​​added. After stirring and mixing, the tea extract is sprayed with a nano nozzle to add 1wt% chitosan solution, and the spraying amount of the chitosan solution is 3ml / 10g. The antibacterial and deodorizing nano tea particles are obtained by drying.

[0059] Preparation of inner protective layer

[0060] Take a non-woven fabric substrate, soak it in a 2wt% sodium carbonate aqueous solution, boil it for 40 minutes, take it out, wash it with clean water until it is neutral, and dry it to constant weight to obtain an activated non-woven fabric substrate. Then take the antibacterial and deodorizing nano white tea particle tea extract and add water to adjust the solid-liquid ratio to 5g / L. After stirring and dispersing, a suspension is obtained. The activated non-woven fabric substrate is horizontally spread on a tray, and the suspension is sprayed onto the surface of the activated non-woven fabric substrate. The spraying amount is 8g / ㎡, and then high-energy electron irradiation treatment is carried out under a nitrogen atmosphere. The irradiation dose is 40kGy. The spraying and irradiation treatment are repeated twice to obtain an inner protective layer.

[0061] The prepared inner protective layer is compounded with the middle layer and the outer layer using an existing conventional method to obtain the nano antibacterial and anti-odor tea mask of the present application.

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that the spraying amount of the suspension in this comparative example is 7 g / m2.

[0064] Comparative Example 2

[0065] The difference between this comparative example and Example 1 is that the spraying amount of the suspension in this comparative example is 11 g / m2.

[0066] Experiment 1 Hydrophilicity Test

[0067] The hydrophilicity and hygroscopicity of the inner protective layer prepared in Examples 1 to 3, Comparative Example 1 and Comparative Example 2 were tested. The existing polypropylene inner protective layer was used as a comparison. Assuming that the side close to the middle layer is the back side and the side close to the human body is the front side, the contact angles of both the front and back sides were tested.

[0068] The specific operation of moisture absorption detection is:

[0069] After cleaning and drying the beaker, add deionized water, place the sample with the back facing upward on the beaker, fix it in an electric constant temperature drying oven (temperature 38°C, relative humidity 2%, airflow 0.5m / s), weigh it after 30 minutes of balance to get m1, repeat the test after 1 hour, weigh it for the second time according to the above steps to get m2, and the moisture permeability is calculated by the following formula:

[0070] WVT=24Δm / St

[0071] In the formula: WVT: moisture permeability [g / (m 2 ·d)], t: moisture permeation time (h), Δm: weight difference between two weighings of the same sample (g), S: moisture permeation area of ​​the sample (m 2).

[0072] The test results are shown in Table 1:

[0073] Table 1. Test results

[0074] project Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example 1 Comparative Example 2 existing Hydrophilic corner (front) 94° 95° 93° 94° 80° 94° Hydrophilic corner (back) 72° 70° 74° 76° 75° 94° Moisture permeability 2.63 2.67 2.65 2.51 2.36 2.21

[0075] It can be seen from the data in Table 1 that the antibacterial and anti-odor particles of the present invention can significantly increase the hydrophilicity of the inner protective substrate, thereby making the inner protective layer have better moisture permeability. From the comparison of the data of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that when the suspension is sprayed too little, due to the small amount of antibacterial and anti-odor particles introduced, the modification of the inner protective substrate is relatively low, and therefore the moisture permeability is relatively low. When the suspension is sprayed too much, since it penetrates into the inner protective substrate, the hydrophilicity difference on both sides of the inner protective substrate is similar. In addition, the increase of antibacterial and anti-odor particles leads to a decrease in moisture permeability.

[0076] Experiment 2: Determination of stability of nano-tea particles

[0077] The stability of tea nanoparticles was determined using a dynamic laser light scattering instrument, Zetasizer Nano S, at 4°C. The test results are as follows: Figure 2 shown.

[0078] pass Figure 2 It can be seen that the hydrodynamic diameter (size) and size distribution (PDI) of the nano-tea leaves show that at 4°C, the particle size increases on the sixth day, but the PDI remains almost unchanged, indicating its good stability.

[0079] Experiment 3 Antibacterial properties of nano-tea particles

[0080] Will contain 10 7 LB medium (containing 30 mM glucose) of Pseudomonas aeruginosa (PA) with colony forming units (CFU) / mL was incubated with nano-tea leaves of different concentrations at 37°C for 2 h, and then plated on agar plates. The agar plates were incubated at 37°C for 24 h and the number of colonies was calculated. The test results are shown in Figure 2. Figure 3 As shown;

[0081] Will contain 10 7 LB medium (containing 30 mM glucose) of Pseudomonas aeruginosa (PA) with colony forming units (CFU) / mL was incubated with 500 μg / mL nano-tea leaves at 37°C for different periods of time and then plated on agar plates. The agar plates were cultured at 37°C for 24 h and the number of colonies was calculated. The test results are shown in Table 2.

[0082] Table 2. Antibacterial kinetic results of tea nanoparticles loaded with EGCG

[0083]

[0084] The experimental results show that the nano antibacterial tea mask of the present invention and the nano tea particles of the present invention have relatively stable and good antibacterial properties. The addition of nano tea particles can significantly improve the antibacterial activity of the tea mask of the present invention and prolong its antibacterial time, thus having a good antibacterial effect.

[0085] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A new type of nano antibacterial and anti-odor tea mask, characterized in that: The mask comprises an outer layer, a middle layer and an inner protective layer from the outside to the inside, the inner protective layer comprises a non-woven fabric substrate and nano tea particles composited on the non-woven fabric substrate, the nano tea particles are made of tea leaves as raw materials, and tea extract and extraction residue are obtained by extraction, and then the extraction residue is ultrafinely ground and modified to obtain a tea matrix, and then the tea matrix is ​​used to load the tea extract; the preparation method of the nano tea particles comprises the following steps: S1: Take the dried tea leaves, add 80wt% ethanol solution, heat and reflux for extraction for 2h, filter after cooling, concentrate the filtrate by rotary evaporation to obtain tea extract, store it in a sealed container, wash the extract residue and dry it for later use; S2: The dried extraction residue is ultrafinely ground, added to a sodium hydroxide solution, and then carbon disulfide is added, and the mixture is stirred at room temperature for 24 hours. After the reaction is completed, the mixture is centrifuged, the reaction solution is collected, and washed with deionized water until neutral. The obtained product is added to deionized water and stirred evenly, and then frozen at -80°C, and then vacuum dried to obtain a tea matrix; S3: Take tea extract and polylactic acid-glycolic acid copolymer, add them to N,N-dimethylformamide solution, stir and mix to obtain a mixed solution, add the mixed solution to 1wt% Tween-80 aqueous solution under stirring, after the addition is completed, continue stirring to react for 24 hours, and after the reaction is completed, place the reaction product in a dialysis bag and dialyze for 24 hours; S4: freeze-dry the solution in the dialysis bag, add the pretreated tea matrix, stir and mix, spray the tea extract with a nano nozzle, add the chitosan solution, and dry to obtain nano tea particles.

2. A novel nano antibacterial and anti-odor tea mask according to claim 1, characterized in that: The nano tea leaf particles are arranged on one side of the non-woven fabric substrate close to the middle layer.

3. A novel nano antibacterial and anti-odor tea mask according to claim 2, characterized in that: The non-woven fabric substrate is made of polypropylene material.

4. A novel nano antibacterial and anti-odor tea mask according to claim 3, characterized in that: In the step S4, the pretreatment of the tea substrate precursor is specifically as follows: dissolving acrylic acid in water, adding 20wt% sodium hydroxide solution to adjust the pH to 5-6, then adding the tea substrate, stirring and dispersing evenly, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, heating to 60-70°C, stirring and reacting for 3-5h, filtering after the reaction is completed, soaking the filter cake in distilled water for 4-6h, then rinsing with deionized water for 3-5 times, and drying.

5. A novel nano antibacterial and anti-odor tea mask according to any one of claims 1 to 4, characterized in that: The preparation method of the inner protective layer is as follows: activating a non-woven fabric substrate to obtain an activated non-woven fabric substrate, then taking a tea extract of nano-tea particles, adding water, stirring and dispersing to obtain a suspension, horizontally laying the activated non-woven fabric substrate on a tray, spraying the suspension onto the surface of the activated non-woven fabric substrate, and then performing high-energy electron irradiation treatment under a nitrogen atmosphere, repeating the spraying and irradiation treatment 2-3 times to obtain the inner protective layer.

6. A novel nano antibacterial and anti-odor tea mask according to claim 5, characterized in that: The activation treatment is as follows: taking the non-woven fabric substrate, boiling it with a sodium carbonate aqueous solution for 40 minutes, taking it out, washing it with clean water until it is neutral, and drying it to a constant weight.

7. A novel nano antibacterial and anti-odor tea mask according to claim 6, characterized in that: The amount of the nano-tea leaf particle suspension sprayed each time is 8-10 g / ㎡.

Citation Information

Patent Citations

  • Antibacterial mask and manufacturing process thereof

    CN111329142A

  • Preparation process of tea-flavor mask

    CN112841773A